(untitled) (Journal of Economic Research & Business Administration, 2022)
The formation of user paths on the way to conversion, customer touch points with the brand, funnel and their evaluation are current issues in the field of marketing. Despite the rapid spread of technology, there are still no general established user guidelines for analyzing the marketing activities of enterprises in combination with the use of analysis tools. The main purpose of this study is the use of analysis tools in working with big data, as well as the ability to evaluate the implementation of tracking the user path from the moment the ad is displayed to the completion of targeted conversions in the final product. The article discusses one of the most advanced analytics systems - Google Analytics, also known as end-to-end analytics, which provides companies with opportunities to conduct basic analysis. Based on this tool, the article carried out work on the implementation of Google Analytics in the «Avtobys» application operating in the field of e-commerce. As a result of the work, unified recommendations for the implementation of an analytics system for applications were developed. Application performance criteria are defined. A model of user behavior in the application was modeled. Key words: Google Analytics, user behavior, marketing attribution, end-to-end analytics, funnel, user journey.